In-vivo Platelet Activation and Anomalous Thrombospondin Levels in Severe Falciparum Malaria. - Supanaranond, W; Davis, T; Dawes, J; Silamut, K; Vilaiwanna, N; White, N (Informa Healthcare, 1992)
To investigate in vivo platelet function in acute falciparum malaria plasma concentrations of β-thromboglobulin (β-TG), platelet factor 4 (PF4) and thrombospondin (TSP) were determined in 10 severely-ill Thai patients and 11 healthy volunteers. 8 patients recovered. At presentation, the platelet counts of the 10 patients were significantly lower (p < 0.025) than those of the controls, and a slight but significant increase (p < 0.05) in β-TG/PF4 ratios in the patients suggested low-grade platelet activation. Presentation plasma β-TG and PF4 concentrations did not differ from control values, probably due to the opposing effects of decreased circulating platelet mass and increased activation. By contrast, admission concentrations of TSP in the surviving patients were markedly lower (p < 0.001) than those of the controls; β-TG/PF4 ratios, but not TSP levels, returned to normal during treatment. Hepatic dysfunction and oliguric renal failure probably contributed to a sustained increase in plasma β - TG and TSP in the 2 fatally ill patients, but associated elevated PF4 levels indicated concomitant platelet activation. Our results support the suggestion that in vivo platelet activation, which appears to be rapidly controlled by treatment, occurs in patients with severe, non-fatal falciparum malaria. TSP production, apparently from non-platelet sources, was decreased and/or its consumption was increased in these patients, perhaps by factors such as cytoadherence of infected erythrocytes and consequent endothelial damage.